(3cJGH GdYjfs - (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jHdZ QVGg gPG cJGH CeQ HLeYI hJCdja CejQ GdeDefjf GdMce GdeSJfUQ HGddg PgH ajg Edi GNJUGQ GdcJGH GdeYQha HcJGH GdYjf GdefShH Edi GdNdjd Hf CMeO GdaQGgjOi HCf jDNP Yfg Yjhfg s
(3BNQgG (B:s
(3hjbGd (B: (3hGh EJUGd GdhGhGJ hGdjGAGJ GfJgi MQa GdjGA MQa GdhGh bGd HYVge Ke JMPa GdhGh , hHJeGeg Je LejY GdMQha HYhf Gddg s
(3fSNI KGdKIs
(3fbdJ Yf fSNI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
Keywords: (3GddZIs